Absence Seizure Detection Algorithm for Portable EEG Devices - Glaba, Pawel; Latka, Miroslaw; Krause, Małgorzata J.; Kroczka, Sławomir; Kuryło, Marta; Kaczorowska-Frontczak, Magdalena; Walas, Wojciech; Jernajczyk, Wojciech; Sebzda, Tadeusz; West, Bruce J. (Frontiers in Neurology, 2021)
Absence seizures are generalized nonmotor epileptic seizures with abrupt onset and termination. Transient impairment of consciousness and spike-slow wave discharges (SWDs) in EEG are their characteristic manifestations. This type of seizure is severe in two common pediatric syndromes: childhood (CAE) and juvenile (JAE) absence epilepsy. The appearance of low-cost, portable EEG devices has paved the way for long-term, remote monitoring of CAE and JAE patients. The potential benefits of this kind of monitoring include facilitating diagnosis, personalized drug titration, and determining the duration of pharmacotherapy. Herein, we present a novel absence detection algorithm based on the properties of the complex Morlet continuous wavelet transform of SWDs. We used a dataset containing EEGs from 64 patients (37 hours of recordings with almost 400 seizures) and 30 age and sex-matched controls (9 hours of recordings) for development and testing. For seizures lasting longer than two seconds, the detector, which analyzed two bipolar EEG channels (Fp1-T3 and Fp2-T4), achieved a sensitivity of 97.6% with 0.7/hour detection rate. In the patients, all false detections were associated with epileptiform discharges, which did not yield clinical manifestations. When the duration threshold was raised to three seconds, the false detection rate fell to 0.5/hour. The overlap of automatically detected seizures with the actual seizures was equal to ∼96%. For EEG recordings sampled at 250 Hz, the one-channel processing speed for midrange smartphones running Android 10 (about 0.2 s per 1 min of EEG) was high enough for real-time seizure detection.